Prevalence of high flow nasal cannula therapy use for management of infants with bronchiolitis in Australia and New Zealand. (6th September 2022) - O'Brien, Sharon; Haskell, Libby; Schembri, Rachel; Gill, Fenella J; Wilson, Sally; Borland, Meredith L; Oakley, Ed; Dalziel, Stuart R
Abstract : Aim: To determine the prevalence of high flow nasal cannula (HFNC) therapy in infants presenting to hospital in Australia and New Zealand with bronchiolitis over four bronchiolitis seasons. Secondary aims were to determine temporal trends in HFNC use, and associations between HFNC, hospital length of stay (LOS) and intensive care unit (ICU) admission. Methods: A planned sub‐study of a multi‐centre international cluster randomised controlled trial investigating knowledge translation strategies for a bi‐national bronchiolitis guideline. Demographics, management and outcomes data were collected retrospectively for infants presenting with bronchiolitis to 26 hospitals between 1 May 2014 and 30 November 2017. Prevalence data are presented as absolute frequencies (95% confidence interval (CI)) with differences between groups for continuous and categorical variables analysed using linear and logistic regression, respectively. Results: 11 715 infants were included with 3392 (29.0%, 95% CI (28.1–29.8%)) receiving oxygen therapy; of whom 1817 (53.6%, 95% CI (51.9–55.3%)) received HFNC. Use of oxygen therapy did not change over the four bronchiolitis seasons ( P  = 0.12), while the proportion receiving HFNC increased (2014, 336/2587 (43.2%); 2017, 609/3720 (57.8%); P  ≤ 0.001). Infants who received HFNC therapy were not substantially different to infants who received oxygen therapy without HFNC. HFNC use was associated with increases in both hospital LOS ( P  < 0.001) and ICU admissions ( P  < 0.001). Conclusion: Use of HFNC therapy for infants with bronchiolitis increased over 4 years. Of those who received oxygen therapy, the majority received HFNC therapy without improvement in hospital LOS or ICU admissions. Strategies to guide appropriate HFNC use in infants with bronchiolitis are required.